Caloric restriction reveals a metabolomic and lipidomic signature in liver of male mice. Issue 5 (23rd July 2014) - Jové, Mariona; Naudí, Alba; Ramírez‐Núñez, Omar; Portero‐Otín, Manuel; Selman, Colin; Withers, Dominic J.; Pamplona, Reinald
Summary Lipid composition, particularly membrane unsaturation, has been proposed as being a lifespan determinant, but it is currently unknown whether caloric restriction (CR), an accepted life‐extending intervention, affects cellular lipid profiles. In this study, we employ a liquid chromatography quadrupole time‐of‐flight‐based methodology to demonstrate that CR in the liver of male C57BL/6 mice: (i) induces marked changes in the cellular lipidome, (ii) specifically reduces levels of a phospholipid peroxidation product, 1‐palmitoyl‐2‐glutaryl‐sn‐glycero‐3‐phosphatidylcholine, (iii) alters cellular phosphoethanolamine and triglyceride distributional profiles, (iv) affects mitochondrial electron transport chain complexes, increasing complex II and decreasing complex III and (v) is associated with specific changes in liver metabolic pathways. These data demonstrate that CR induces a specific lipidome and metabolome reprogramming event in mouse liver which is associated with lower protein oxidative damage, as assessed by mass spectrometry‐based measurements. Such changes may be critical to the increased lifespan and healthspan observed in C57BL/6 mice following CR.